Konversi Pelumas SAE 5W-30 Bekas Menjadi Bahan Bakar Cair Dengan Proses Hydrocracking Berbasis Katalis - Yohandri Bow; Sutini Pujiastuti Lestari; Fatria Fatria; Muhammad Reza Ramlan; Heru Afriansyah; Miranda Roulina (Jurnal Teknologi, 2021)
The number of passenger automobiles, buses, cargo cars, and motorcyclists on the road in Indonesia continues to rise year after year. According to the Central Statistics Agency, the number of transportation equipment in 2015 was 105,303,318 million, up 6.5 percent from the previous year. In 2016, it was 112,205.711 million, up 6.5 percent. As can be seen from the above, Indonesia's transportation options are expanding throughout time. As a result, the demand for lubricants rises as well. As the need for lubricants grows, so does the amount of spent lubricants that is thrown away. Water absorption is inhibited by used lubricant waste that is disposed of in the soil. Given the aforementioned issues, a solution for converting spent lubricant waste into something more useful, such as liquid fuel, is required. Making a prototype for turning spent SAE 5W-30 lubricant waste into liquid fuel using the hydrocracking method with the help of a Ni/ZAA catalyst is one approach to go about it. The effect of temperature fluctuations of 300 °C, 350 °C, 400 °C, 450 °C, and 500 °C was employed as the independent variable in this investigation. The amount of used lubricant feed used in this investigation is 641.10 ml, which is a fixed variable. The best yield values were obtained at a temperature of 400 °C with a cetane number of 76.2, which met the diesel requirement.